Mitreola bullata sp. nov. (Loganiaceae), a new species from Yunnan, China - Liao, Jun-Jie; Chen, You-Shen (Phytotaxa, 2021)
Mitreola bullata sp. nov. (Loganiaceae), a new species from southeastern Yunnan, China, is described and illustrated. This species is somewhat close to M. yangchunensis, but differs by its low height, leaf blades bullate and densely pilose on both surface, petioles longer and purple or green, veins on abaxial surface purple, and calyces glabrous and purplish red. A key to all the species of Mitreola in China is provided.